Controlled Aerobic Oxidation of Primary Benzylic Alcohols to Aldehydes Catalyzed by Polymer-Supported Triazine-Based Dendrimer–Copper Composites - Pan, Shiguang; Yan, Shuo; Osako, Takao; Uozumi, Yasuhiro (Synlett, 2018)
A controlled aerobic oxidation of primary benzylic alcohols to the corresponding benzaldehydes by using polystyrene–poly(ethylene glycol) (PS–PEG) resin-supported triazine-based polyethyleneamine dendrimer–copper complexes [PS–PEG-TD2–Cu(II)] was developed. In particular, PS–PEG-TD2–Cu(OAc)2 efficiently catalyzed the aerobic oxidation of benzylic alcohols in the presence of a catalytic amount of TEMPO under atmospheric conditions to give the corresponding aldehydes in up to quantitative yield. The catalyst was readily recovered by simple filtration and reused four times without significant loss of its catalytic activity.
Keywords: dendrimer; aldehydes; aerobic oxidation; polymer support; copper catalysis